Improvement of the Ability to Recognize the Letters A-Z with the Letter Detective Method in Raudlatul Athfal - Daswati, Daswati (FITK UIN Walisongo Semarang, 2024)
This research aims to improve the ability to recognize letters in children in group B of RA Hidayatul Islam Bendo by applying the letter detective method. This study uses a classroom action research design (PTK), with research subjects consisting of 12 children. Data collection is carried out through three main techniques, namely observation, performance, and documentation, which aims to obtain comprehensive information related to the development of literacy skills in children. The data analysis techniques used involve quantitative and qualitative descriptive analysis. The success of this study was measured by the criterion that at least 85% of the children who were the subjects of the study could know the letters well. The results of the study showed that the use of the letter detective method, which was equipped with the media of letter cards, significantly improved the ability to recognize letters in children. In the pre-cycle stage, only 33% of children are able to recognize letters well. However, after the application of the letter detective method, there was a gradual increase, with a result of 50% in cycle I, 67% in cycle II, and reaching 92% in cycle III. Thus, this method has proven to be effective in improving letter recognition in children, and can be used as one of the interesting and interactive teaching strategies in letter recognition learning at the early childhood education level